IDENTIFICATION OF CHALLENGES AND OPPORTUNITIES IN ONLINE LEARNING OF ISLAMIC MATERIAL IN DAYAH-BASED SENIOR HIGH SCHOOL - Rizal, Muhammad; Zulfikar, T.; Syabuddin, Syabuddin; Iskandar, Iskandar (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study was to examine the implementation of online learning-based Islamic Religious Education (PAI in high schools in the Dayah environment. This research use desciptive qualitative approach. The subjects of this research were maple PAI teachers at junior and senior high schools in the Dayah area. Data were collected through observation, interviews with PAI teachers and students, and documentation using descriptive-analytic analysis techniques. The research was conducted in the 2022/2023 school year November-February 2023. The results of this study underlined the opportunities that occur in PAI learning in the Dayah environment, namely (1) ability to use technology applications, (2) development of teacher competence in ICT, (3) maintain students' interest in learning PAI. Meanwhile, the challenges faced by elementary school teachers and students in online learning at Dayah are (1) difficulties in accessing technology facilities, (2) Dayah rules which prohibit independent use of technology facilities, (3) Limited funds for operational implementation of digital schools, (4) loss learning so that it is easy to access negative things. The gains from online learning opportunities cannot be overlooked either. The accumulation and formulation of a number of opportunities and challenges presented above will be a positive synergy for the development of technological developments and the forerunners of modernization of the next Dayah education system.